THE IMPORTANCE OF RECOVERY TOOLS IN ATHLETES - Akbarova D. R.; Fuzailova E. M.; Olimova D. T. (Proximus Journal Publishing, 2024)
This article provided information on improving the performance of athletes, training methods, and control of the size and intensity of loads, the fact that an increase in loads can negatively affect the health of athletes, their functional state, and the types of recovery tools, as well as their importance to the body.
Keywords: athlete; health; fatigue; recovery